58 The Benefits of A Virtual Ward Model in the Management of Care of Elderly Patients Admitted with Decompensated Heart Failure. (16th March 2021) - Reid, P; Kandasamy, V; Chambers, B; Tomos, L; Procter, H; Pushpangadan, M; Bulugahapitiya, S
Abstract: Introduction: Heart failure in elderly patients is associated with increasing rates of hospitalisation and readmission. The Care of Elderly department at Bradford Royal Infirmary has developed a virtual ward service to support patients at home on discharge from hospital. We wished to assess if patients admitted with heart failure and discharged under the virtual ward model had a reduced length of stay in hospital and if their readmission rate was altered, compared to patients not discharged under the virtual ward. Method: A retrospective study of patients admitted under the Care of Elderly team with decompensated heart failure was undertaken. Patients admitted over 12 months were identified and assessed length of stay and readmission rates at 7 and 30 days post admission. There were no set criteria for discharge to the virtual ward, but patients were selected for virtual ward care based on; symptom burden, renal function and ongoing PT/OT support. Results: Of the 358 patients identified in this study, 83 (23%) were discharged to the virtual ward (VW). On average patients spent 7 days (+/− 5.3) under the virtual ward service. Average length of hospital stay for VW patients was 2.3 days compared to 6.5 days for patients not discharged under the virtual ward (p < 0.0001). Of the patients discharged to the virtual ward, 8 (10%) were readmitted within 7 days and 23 (28%) were readmitted within 30 days, similar to readmission rates in patients not discharged under the virtual ward with 25 (11%) and 62 (27%) patients readmitted after 7 and 30 days respectively. Conclusions: The use of a virtual ward service model for selected elderly patients with heart failure reduces the length of inpatient stay. The virtual ward service model, compared to conventional care, did not increase readmission rates in our study.